Simultaneous acute deep vein thrombosis and acute brucellosis. A case report - Salihi, Salih; Andaç, Şeyda; Kalender, Mehmet; Yıldırım, Onur; İmre, Ayfer (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Brucellosis is a zoonotic disease common in developing countries. Vascular complications, including arterial and venous, associated with Brucella infection have rarely been reported. A case of deep venous thrombosis (DVT) developing after a diagnosis of acute brucellosis in a young milkman is presented. A 26-year-old man presented with pain in the right leg. The patient’s medical history included a diagnosis of brucellosis in our hospital where he had presented with complaints of weakness and fever. Peripheral venous Doppler ultrasound showed DVT, and the patient was treated with anticoagulants. The patient was discharged with warfarin therapy and anti-brucellosis treatment. Although rare, some infectious agents may cause vascular pathologies. Patients presenting with symptoms of DVT or similar vascular pathologies should be assessed for infectious agents, particularly in those coming from Brucella -endemic areas.